Computational Analysis for Dam Stability Against Water Flow Pressure. Issue 1 (1st January 2023) - Tulus,; Marpaung, T J; Marpaung, J L
Abstract: Fatigue analysis of an object's structure is very important because it can provide a numerical value that can be used as a reference before acting. The finite element method is a numerical method that can calculate the value of the fatigue and stability of a structure by calculating the reynold value and the pressure given. This study aims to conduct a structural fatigue analysis of the dam that focuses on the Reynold value in order to provide an analysis and representation of the dam structure. The result to be achieved is a mathematical model that analyzes the fatigue of the dam structure by connecting the elevation angle, water velocity, time, and the force obtained from the kinetic energy in the water flow.